Evaluasi Kondisi Mental Peserta Didik Siswa SMA Dalam Kekhawatiran Terkait Penggunaan Jejaring Sosial - Leni Anggraeni; Sariyah Astuti; Tri Yuni Hendrowati; Nurlela Nurlela (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Today's education demands effective and efficient human resource management. For communities to effectively manage Today's students' lives are highly dependent on social media, which has both positive and negative impacts on their ability to acquire knowledge. This study aims to evaluate the psychological readiness of high school students in using online social networks, using the psychological preparation method. Two researchers were interviewed extensively to explore their personal experiences using qualitative phenomenological inquiry techniques. The results of the study indicate that peer support, psychological control, and adaptive capacity in facing various obstacles, including harassment and violence, are indicators of students' mental readiness. Adaptive students generally choose inspiring knowledge, have problem-solving techniques, and successfully utilize them. Based on these findings, this study suggests strategies such as improving basic knowledge about technology and conducting psychological management teaching and developing supportive conditions in collaboration with students and their families. The results of this study emphasize the importance of a comprehensive approach to fostering students' resilience to change in an environment of rapid technological advancement.